LEARNING OUTCOMES: SOCIAL SUPPORT, SELF-CONFIDENCE, AND ECONOMIC LEARNING MOTIVATION - Zahar, Erlina; Masni, Harbeng; Hutabarat, Zuhri Saputra; Pratiwi, Heni; Tara, Firman; Sujoko, Sujoko; Andriani, Lili; Aziza, Aziza (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
This research aims to find out the indirect influence of Self-Confidence on Learning Outcomes through the economics learning motivation of Class XI Students at SMK Negeri 2 Jambi City. This type of research is causal associative using a quantitative approach. This research was conducted at SMK Negeri 2 Jambi City. The method used is a survey method through distributing questionnaires from a population and sample of 124 people, using a saturated sampling technique or census. Data processing uses SPSS Amos (Statistical Product and Service Solution) version 17.1 for Windows 8. The results of this research show that: 1) There is a significant positive influence between social support on learning outcomes of 0.455, t count > t table, namely 5,640 > 1.67. 2) There is a positive and significant influence between self-confidence on learning outcomes of 0.402, t count > t table, namely 4,849 > 1.675. 3) There is a positive and significant influence between motivation on learning outcomes of 0.419, t count > t table, namely 1.675 > 0.05. 4) There is a positive and significant influence between social support and motivation of 0.272, t count > t table, namely 3,119 > 1,655. 5) There is a positive and significant influence between the work environment on work motivation of 0.844, t count > t table, namely 10.177 > 2.015. 6) There is a positive and significant indirect effect between support for economic learning outcomes through motivation of 0.559, F hit > F table or 518.919 > 2.698. 7) There is a positive and significant indirect influence between self-confidence on learning outcomes through motivation of 0.504, F hit > F table or 18.919 > 2.68. This research concludes that there is a positive and significant influence between social support, self-confidence, and motivation for the economic learning outcomes of class XI students at SMK Negeri 2 Jambi City. Without ignoring other factors that can also influence Economics learning outcomes. In an effort to improve economic learning outcomes, students should increase their sense of ownership and awareness of responsibility and comply with applicable policies for the common good